Psychometric properties of the Japanese translation of the De Jong Gierveld Loneliness Scale for young and older adults - Arai, Honami; Okawa, Sho (Frontiers in Psychology, 2025)
ObjectiveThe De Jong Gierveld Loneliness Scale (DJGLS) has been widely used to measure two types of loneliness: social and emotional loneliness. However, no Japanese translation has been developed. Furthermore, the characteristics of social and emotional loneliness in the Japanese population remain unclear. This study examined the psychometric properties of a Japanese translation of the DJGLS.MethodsA total of 1,000 participants (500 young and older adults each) completed online questionnaires, which included items on loneliness, depression, and social isolation.ResultsConfirmatory factor analyses revealed a two-correlated factor structure for the Japanese translation of the DJGLS in both young and older adults. McDonald’s omega coefficient was high for both social and emotional loneliness. The emotional loneliness subscale was moderately correlated with general loneliness and depression. Furthermore, the social loneliness subscale was moderately correlated with general loneliness and social isolation. Depression was more strongly correlated with emotional loneliness than with social loneliness. Item response theory demonstrated the characteristics of each item in the Japanese translation of the DJGLS.ConclusionThese results support the validity and reliability of the DJGLS among young and older Japanese adults.